Exercise-induced IL-15 acted as a positive prognostic implication and tumor-suppressed role in pan-cancer - Luo, Zhiwen; He, Zhong; Qin, Haocheng; Chen, Yisheng; Qi, Beijie; Lin, Jinrong; Sun, Yaying; Sun, Junming; Su, Xiaoping; Long, Ziwen; Chen, Shiyi (Frontiers in Pharmacology, 2022)
Objective: Exercise can produce a large number of cytokines that may benefit cancer patients, including Interleukin 15 (IL-15). IL-15 is a cytokine that has multiple functions in regulating the adaptive and innate immune systems and tumorigenesis of lung and breast cancers. However, the roles of IL-15 in other types of cancer remain unknown. In this article, we try to systematically analyze if IL-15 is a potential molecular biomarker for predicting patient prognosis in pan-cancer and its connection with anti-cancer effects of exercise. Methods: The expression of IL-15 was detected by The Cancer Genome Atlas (TCGA) database, Human protein Atlas (HPA), and Genotype Tissue-Expression (GTEX) database. Analysis of IL-15 genomic alterations and protein expression in human organic tissues was analyzed by the cBioPortal database and HPA. The correlations between IL-15 expression and survival outcomes, clinical features, immune-associated cell infiltration, and ferroptosis/cuproptosis were analyzed using the TCGA, ESTIMATE algorithm, and TIMER databases. Gene Set Enrichment Analysis (GSEA) was performed to evaluate the biological functions of IL-15 in pan-cancer. Results: The differential analysis suggested that the level of IL-15 mRNA expression was significantly down-regulated in 12 tumor types compared with normal tissues, which is similar to the protein expression in most cancer types. The high expression of IL-15 could predict the positive survival outcome of patients with LUAD (lung adenocarcinoma), COAD (colon adenocarcinoma), COADREAD (colon and rectum adenocarcinoma), ESCA (esophageal carcinoma), SKCM (skin cutaneous melanoma), UCS (uterine carcinosarcoma), and READ (rectum adenocarcinoma). Moreover, amplification was found to be the most frequent mutation type of IL-15 genomic. Furthermore, the expression of IL-15 was correlated to the infiltration levels of various immune-associated cells in pan-cancer assessed by the ESTIMATE algorithm and TIMER database. In addition, IL-15 is positively correlated with ferroptosis/cuproptosis-related genes (ACSL4 and LIPT1) in pan-cancer. Conclusion: Our results demonstrated that IL-15 is a potential molecular biomarker for predicting patient prognosis, immunoreaction, and ferroptosis/cuproptosis in pan-cancer and partly explained the anti-cancer effects of exercise.